Value Crisis in SMEs Branding Communication: A Systematic and Bibliometric Study of Business Ethics Transformation - Sri Hartati; Edwin Karim; Naufal Shayed Alam; Fanji Wijaya (Jurnal Moral Kemasyarakatan, 2025)
In today’s complex digital and ethical business environment, MSMEs face increasing tension between market-driven branding strategies and the integration of authentic ethical values. This study identifies a core problem in the literature: a persistent fragmentation between performance-oriented branding and ethics-oriented communication within MSME practices. Using a Systematic Literature Review (SLR) guided by PRISMA 2020 and supported by bibliometric tools (Bibliometrix and VOSviewer), we analyzed 79 Scopus-indexed articles published between 2015 and 2025. The analysis reveals three dominant conceptual clusters: (1) digital branding and social media, (2) sustainability and CSR integration, and (3) ethical legitimacy and stakeholder value. Despite increasing attention to sustainability, ethical dimensions often remain symbolic or fragmented. As a response, this study proposes a novel framework integrating digital strategy, value-based sustainability, and ethical stakeholder legitimacy. The study contributes a conceptual foundation for future research and offers practical guidance for branding strategies that are not only performative but also ethically grounded and socially legitimate.